The effect of late diagnosis on survival and risk of vascular complications in Takayasu's arteritis patients - I. E. Borodina; A. A. Popov; L. A. Shardina (Научно-практическая ревматология)
Aim. To assess the effect of late diagnosis on survival and risk of vascular complications in Takayasu's arteritis (TA) patients.  Methods. 183 patients with TA who were treated at the Sverdlovsk Regional Clinical Hospital No. 1 during the period from 01.01.1979 to 31.04.2018 were examined. There were 139 women and 44 men included, median age at the time of diagnosis being 35 [24; 44] years in females and 34 [26.5; 42] years in males and a median interval from the first symptoms onset to the diagnosis of 3 [1; 7] and 4 [1.5; 8] years respectively. The diagnosis of TA met the ACR criteria (1990).Results. During the follow-up period, 31 deaths were observed (18 in males and 13 in females). The median age of death for women was 36 [32-44] years, for men - 50 [40-57] years. Cardiovascular complications were recorded in 72 patients (27 men and 45 women). Vascular complications and namely acute cerebrovascular accident observed in 31 (43%) patients, including ischemic stroke in 24 (35%), transient ischemic attack in 3 (3%) and hemorrhagic stroke in 4 (6%) were the most frequent. Arterial thromboses were registered in 32 (44%) cases. In 162 (88.5%) patients, the diagnosis was established more than six months after the appearance of the first symptoms.At the primary physician visit in 71 (39%) patients, the initial diagnosis was erroneous. The most common symptoms they had were regarded as a manifestation of arterial hypertension (in 18% cases). 4 years or more interval from the onset of TA symptoms to diagnosis was associated with a significant cardiovascular events odds increase (OR=1.8; 95% CI: 1.07-3.34) and premature death by the 5th year of follow-up (OR=2.9; 95% CI: 1,27-6,55).Conclusion. In the retrospective TA cohort setting, late diagnosis verification and delayed treatment initiation were associated with an increased risk of premature death and severe vascular complications, described earlier in other samplings. Timely diagnosis and as early as possible appropriate treatment administration can prevent the disease progression and disabling complications occurrence.